The trust imperative : performance improvement through productive relationships - Hacker, Stephen, 1955- (ASQ Quality Press, 2002)
Annotation Todayes businesses environment is highly demanding and increasingly competitive, requiring organizations to be flexible, responsive, and continually innovative. In order for this to happen, there must be a high degree of trust throughout the organization. Leaders need to trust that their workers will carry out their directives, and employees need a high level of trust in the vision and direction that leaders create for the organization. Without this trust an organization will struggle to reach its goals and attain the success desired. This is the focus of The Trust Imperative: Performance Improvement Through Productive Relationships, by Steven Hacker and Marsha Willard, which explains how to develop trust throughout an organization, while improving performance and increasing productivity. Many organizations have major problems as they try to gain the trust of their own personnel, as well as the trust of their customers and suppliers. In many cases, an organizationes attempts to gain trust lack credibility and create more problems than they solve. The Trust Imperative helps break through these obstacles, by offering a straightforward method for assessing trust across an organization. the book offers simple conceptual models, assessments, and trust tools which will help individuals diagnose, measure, and improve the level of trust within the organization. the authors then provide succinct tips and techniques to support the continuous development of trust within any organization.
Keywords: Organizational behavior.; Trust.; Interpersonal relations.; elektronické knihy; electronic books